Fonetyczno-akustyczna analiza struktury sylaby w języku polskim na potrzeby technologii mowy - Śledziński, Daniel (Investigationes Linguisticae, 2008)
This paper presents results of investigations concerning the role of syllable as the main unit for automatic speech recognition and speech synthesis for Polish. Research reveals that the acoustic properties of the particular syllable make it easy detectable in the speech signal. The artificial neural networks were used for classification tasks. Also auditory test showed that use of syllables is good solution for speech synthesis. The article presents parts of author`s doctor thesis: ‘Acoustic-phonetic analysis of syllable in Polish for use in speech technology’.